2011
DOI: 10.1016/j.dss.2011.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Contextual constraints in media choice: Beyond information richness

Abstract: In today's dynamic environment, managers and organizations are faced with varied choices in communicating information for enhanced decision making. In business, the selection of the appropriate media needs to be efficient and effective for decision making and can be crucial in certain circumstances. Recent studies have relied on numerous theories to explain media choice. This research work goes beyond the traditional task characteristics of equivocality and uncertainty from the media richness theory. It addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…Thus, we considered intention to purchase as an inappropriate dependent variable for households that already owned household technologies. Although some technology acceptance research has employed intention as a dependent variable, even in cases where the behavior is well rehearsed (Bhattacherjee, 2001a;Djamasbi et al, 2010;Lee, 2009;Luo et al, 2011;Pavlou & Fygenson, 2006;Thompson, Higgins, & Howell, 1991), much research in psychology (Aarts & Dijksterhuis, 2000;Gollwitzer & Sheeran, 2006;Ouellette & Wood, 1998;Sheeran, 2002) and technology acceptance (Ortiz de Guinea & Markus, 2009;Palvia, Pinjani, Cannoy, & Jacks, 2011) has demonstrated that intentions are typically important only in the context of new behaviors and are not predictive for well-rehearsed, routinized behaviors. Therefore, we employ use behavior as the dependent variable for those that have already adopted a particular household technology.…”
Section: Purchase Versus Usementioning
confidence: 99%
“…Thus, we considered intention to purchase as an inappropriate dependent variable for households that already owned household technologies. Although some technology acceptance research has employed intention as a dependent variable, even in cases where the behavior is well rehearsed (Bhattacherjee, 2001a;Djamasbi et al, 2010;Lee, 2009;Luo et al, 2011;Pavlou & Fygenson, 2006;Thompson, Higgins, & Howell, 1991), much research in psychology (Aarts & Dijksterhuis, 2000;Gollwitzer & Sheeran, 2006;Ouellette & Wood, 1998;Sheeran, 2002) and technology acceptance (Ortiz de Guinea & Markus, 2009;Palvia, Pinjani, Cannoy, & Jacks, 2011) has demonstrated that intentions are typically important only in the context of new behaviors and are not predictive for well-rehearsed, routinized behaviors. Therefore, we employ use behavior as the dependent variable for those that have already adopted a particular household technology.…”
Section: Purchase Versus Usementioning
confidence: 99%
“…In multi-channel retail, the proliferation of digital channels provide consumers with abundant information from multiple channels to conduct online shopping task. In this case, these channels' information content could influence the relative effects of online channel media richness on decision-making and channel choice [26]. Information content is associated with the degree of information accuracy, consistency, and reliability [27].…”
Section: Introductionmentioning
confidence: 99%
“…As experience attribute is more ambiguous and abstract, consumers will need to reconstruct different pieces of information into an overall product evaluation (Coupey 1994;Johnson 1988;Johnson and Russo 1984). According to the information richness theory, highly ambiguous and uncertain attributes which create more latitude for judgment are important factors in accounting for superior performance of information richness (Daft and Lengel 1986;Lo and Lie 2008;Palvia et al 2011). Besides, information richness will be higher for personal-oriented subjective message than for functional-oriented objective message (Otondo et al 2008).…”
Section: Product Typementioning
confidence: 99%
“…In other words, highly uncertain messages are in greater need of rich information for lessening misunderstanding in order to ensure transmitting quality (Lo and Lie 2008;Palvia et al 2011). Given that negative information is generally presented with negative consequences and lack of beneficial results, it tends to arouse stronger feelings of outcome uncertainty (Broemer 2002;Fiske 1980;Kaneouse and Hanson 1971).…”
Section: Ewom Valence and Information Richnessmentioning
confidence: 99%
See 1 more Smart Citation